AN INVESTMENT ANALYSIS FOR BUSINESS DIVERSIFICATION STRATEGY IN PT. BPK (The Indonesian Journal of Business Administration, 2019)
The trend of production and consumption of fuel-based energy is increasingly up worldwide. The condition can benefit industry players to run the projects from investments in the sectors. However, PT. BPK, family-run business, is facing fierce competition and uncertainty of income in the future because of the limitedness of small to medium scale projects in the oil and gas industry. Using the approach of Grand Matrix Strategy, this paper is going to find appropriate strategy PT. BPK can take in the future to secure and increase more income and make the company as a going concern. The analysis includes external analysis, inter alia: PEST, Porter Five Force, and competitor analysis, while internal analysis is using VRIO and value chain analysis. These analyses will narrow into SWOT and TOWS, and then being constructed into IFAS and EFAS to formulate the business strategy. The analysis has concluded into diversification strategy as the primary option. PT. BPK is now eyeing on a new project in coal transportation to diversify its business. Investment analysis is feasible as shown by positive project and equity NPV, project IRR is higher than WACC, equity IRR is higher than the cost of equity, and payback period on the investment is faster than the project period.Keywords : Feasibility Study, Financial Analysis, IRR, NPV, WACC